Strategi Pemanfaatan Lahan Di Ruang Terbuka Tepian Sungai Kahayan: Land Utilization Strategy in Open Spaces on the Banks of the Kahayan River - Hamidah, Noor; Frieda, Frieda; Santoso, Mahdi; Nindito, Dwi Anung; Nazwa, Nazwa; Kudadiri, Puput Khairani (JURNAL HUTAN TROPIKA, 2025)
The use of open space on riverside has different characteristics from open space on land. Pahandut Seberang Village is the location of the research on land use in open spaces. The Pahandut Seberang Village area is one of the villages in Pahandut District located on the Kahayan Riverside area. Pahandut Seberang Village can be reached by land transportation or by river. The purpose of this study is to analyze land use strategies in open spaces on the Kahayan Riverside area. The research method uses qualitative methods based on literature studies, surveys, and interviews with residents and key persons. The strategy analysis identified the function of open spaces in the riverside area. The results of the analysis show that land use during high tide and low tide is different in terms of physical spatial functions, and community social activities in the open space. The results of this analysis can be used as a reference in the development of spatial areas on riverside.